2014
DOI: 10.1007/s00125-014-3288-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide binding protein, obesity status and incidence of metabolic syndrome: a prospective study among middle-aged and older Chinese

Abstract: Aims/hypothesis Although microbiota-derived endotoxaemia has previously been shown to induce metabolic disorders, data from population-based longitudinal studies are scarce. This study therefore investigated the associations between lipopolysaccharide binding protein (LBP) levels and 6 year incident metabolic syndrome (MetS), as well as the potentially modifying effects of obesity status in middle-aged and older Chinese men and women. Methods A total of 2,529 men and women aged 50-70 years from Beijing and Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 29 publications
11
50
0
1
Order By: Relevance
“…A recent Chinese study has investigated the association between plasma LBP and the 6-year incidence of MS, and the potential modification effects of obesity status on the LBP-MS association in adults. The authors conclude that elevated plasma LBP is positively associated with 6-year MS incidence, especially among normal-weight individuals [74]. This finding supports the hypothesis that an increased IP and a mild degree subsequent endotoxemia are involved both in MS and fatty liver disease pathogenesis, and might link them together.…”
Section: Nalfd: the Liver At The Centersupporting
confidence: 69%
“…A recent Chinese study has investigated the association between plasma LBP and the 6-year incidence of MS, and the potential modification effects of obesity status on the LBP-MS association in adults. The authors conclude that elevated plasma LBP is positively associated with 6-year MS incidence, especially among normal-weight individuals [74]. This finding supports the hypothesis that an increased IP and a mild degree subsequent endotoxemia are involved both in MS and fatty liver disease pathogenesis, and might link them together.…”
Section: Nalfd: the Liver At The Centersupporting
confidence: 69%
“…Although seemingly unexpected, these findings can be viewed in relation to our current understanding that complex relationships exist between inflammatory pathways (Lbp-null mice also showed a decrease in systemic and local inflammatory markers, such as IL-6) and metabolic regulation. Numerous studies have demonstrated a positive association between serum LBP concentration and obesityassociated metabolic disturbances, including insulin resistance, in humans [29][30][31][32][33]. However, a discrepancy between circulating concentrations of innate immune system proteins in obese patients and the metabolic phenotype of the corresponding knockout mice has also been reported for lipocalin-2 [34,35] and IL-6 [4,36].…”
Section: Discussionmentioning
confidence: 99%
“…LBP is strongly correlated with LPS levels ( r ≥ 0.6) in human serum (11) and increases in response to greater LPS in mouse models (12). Therefore, owing to its crucial role in modulating the immune response and its known correlation with LPS, LBP is generally considered to be a reasonable surrogate biomarker for assessing LPS-induced inflammation in humans (13,14). …”
Section: Introductionmentioning
confidence: 99%
“…LBP levels are higher among individuals who are obese, have diabetes, or have metabolic syndrome or glucose intolerance (1318). Although cross-sectional studies have shown that LBP levels are associated with anthropometric and metabolic measurements (11,15,18), few longitudinal studies have investigated LBP in relation to obesity- and diabetes-related measures (13).…”
Section: Introductionmentioning
confidence: 99%